Control of linear parameter varying systems with applications - Scherer, Carsten W.; Mohammadpour, Javad (Springer US, 2012)
Control of Linear Parameter Varying Systems with Applications compiles state-of-the-art contributions on novel analytical and computational methods to address system modeling and identification, complexity reduction, performance analysis and control design for time-varying and nonlinear systems in the LPV framework. The book has an interdisciplinary character by emphasizing techniques that can be commonly applied in various engineering fields. It also includes a rich collection of illustrative applications in diverse domains to substantiate the effectiveness of the design methodologies and provide pointers to open research directions. The book is divided into three parts. The first part collects chapters of a more tutorial character on the background of LPV systems modeling and control. The second part gathers chapters devoted to the theoretical advancement of LPV analysis and synthesis methods to cope with the design constraints such as uncertainties and time delay. The third part of the volume showcases concrete applications of LPV modeling and control techniques in a wide range of technological areas including automotive engines and vehicles control, wind energy conversion systems, micro-satellites, vibroacoustic systems, aircraft technology, and freeway traffic control.  Controlof Linear Parameter Varying Systems with Applications is an ideal monograph for researchers, graduate students, and practicing engineers specializing in systems theory, optimization and controls, and complex engineered systems.